Sharia Investment and Zakat Distribution Effects on Poverty Reduction in Indonesian Provinces (2020-2024) - Ulfia Nur Afifa; Sulistya Rusgianto (Universitas Alma Ata, 2025)
Introduction: This study aims to analyze the effects of Islamic investment, zakat distribution, gross regional domestic product (GRDP) per capita, and unemployment on poverty levels across Indonesian provinces. The objective is to assess how Islamic finance and macroeconomic indicators contribute to welfare improvement.Methodology: The method applies a static panel data regression using the Random Effect Model (REM) for the 2020–2024 period. Panel estimation captures both cross-sectional and time variations, while the Hausman test confirms the appropriateness of REM. Data are sourced from OJK, BAZNAS, BPS, and the Ministry of Manpower. The data are sourced from the Financial Services Authority of Indonesia (OJK), the National Board of Zakat (BAZNAS), the Central Statistics Agency (BPS), and the Ministry of Manpower.Result: The results show that Islamic investment significantly reduces poverty, emphasizing its role as an effective instrument for welfare. GRDP per capita also has a negative impact on poverty, highlighting the importance of regional economic growth. In contrast, zakat distribution and unemployment are not statistically significant in this model.Conclusion: The novelty of this study lies in combining Islamic social finance and investment variables with conventional macroeconomic factors in a single panel framework. This integration offers a more comprehensive perspective on poverty alleviation, particularly in the Indonesian context after 2020.